The Research of the Intelligent Device Management and Diagnostic - Cao Pan; Jian Tao; Hongyuan Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
By our research and implementation of intelligent device management and diagnostic system which are based on Wireless HART Technology. In this essay we focus on the application of the wireless HART intelligent devices, explaining the wireless HART protocol and its four-level model, putting forward the wireless HART-USB potable gateway, by which the operating personnel at the scene can obtain data for diagnosis and modification directly from the PC. Then we briefly discuss the design module of intelligent device management system. In the end, we mainly emphasize on the introduction of the mathematical model which is based on the pneumatic control regulator and is used for diagnosis. And we represent the steps of verifying its correctness. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1631